Attitude strength moderates adverse effects to questionnaire design. Issue 2 (3rd April 2018) - Bogner, Kathrin; Pforr, Klaus; Menold, Natalja
ABSTRACT: The presentation and visual design of the "don't know" category in rating scales on respondents' behavior may have ambivalent effects. The hypothesis is that attitude strength toward the topic influences the respondents' sensitivity to the graphical design of the scale. A paper-and-pencil questionnaire conducted among 307 German university students contained an experimental variation of the presentation of a "don't know" category and its visual design. A multinomial logistic regression shows that presenting a "don't know" category drives respondents toward extreme categories. The visual design of the "don't know" category influences the distribution of responses, all the more that the respondents' attitudes toward the item topic are weak.